MOLECULAR DETECTION OF MEASLES VIRUS FROM CHILDREN DURING A SPORADIC OUTBREAK IN TWO SEMI-URBAN AREAS IN NIGERIA - Olusola, Babatunde adebiyi; Adeniji, Johnson Adekunle (African Journal of Infectious Diseases (AJID), 2014)
Background: According to the World Health Organization (WHO), African region accounts for 36% of deaths caused by measles worldwide. Nigeria has, over the years, recorded the highest average annual measles incidence per 100,000 populations in Africa. Measles epidemics have consistently been reported in northern Nigeria, but not in the South; reports of reduced protective haemagglutination inhibition antibody titers among children in Ibadan, southern Nigeria was made. Investigation of the viral agent responsible for the disease outbreak among children presenting with rash in two semi urban areas in southern Nigeria was carried out to confirm the etiology of the disease. Methodology: Twenty six throat swabs (TS), and nineteen urine samples were collected from twenty six children residing in Onireke and Sabo areas of Ibadan following the report of an outbreak of rashes among children. Active case finding with the support of community leaders was used to locate the affected children. Multiplex reverse transcriptase polymerase chain reaction (MRT-PCR), was used to identify the agent. Results: 21 of the 26 children screened tested positive for measles virus, but none was positive for Rubella virus. There was significant association between measles infection, and households with higher number of persons. Conclusion: Mass measles vaccination that targets overcrowded, rural and inaccessible areas is needed to increase herd immunity. Public health enlightenment on the benefits of vaccination is encouraged.